Europe–China economic cooperation after official Belt and Road initiative announcement - Roszkowska, Dorota; Matlaszek, Emilia (Overcoming Controversies in East Asia, 2017)
The official announcement of the One Belt One Road (OBOR) initiative in September 2013 opened a new chapter, not only in the economic and political history of the People’s Republic of China (PRC), but also at least 60 other countries, including European ones. Therefore, the OBOR initiative can be considered as an instrument enabling greater Sino-European economic connectivity. There are a few different forms of high-level meetings, organized to create space for European-China discussions. The most significant are EU–China Summits, Asia–Europe Meeting (ASEM), and 16+1 Summits (China–Central Eastern Europe Initiative). The guiding documents, agreed during those events shape in a significant way, future political and economic relations. After September 2013, important conclusions, which are consistent with OBOR presumptions, were made. For example, the the EU–China discussion on a Comprehensive Agreement on Investment (CAI) has started, EU–China Connectivity Platform, has been created. In October 2013, the Peoples Bank of China and the European Central Bank signed a bilateral local currency swap arrangement. Finally, at the beginning of 2016, China became the 67th member of the European Bank for Reconstruction and Development. Despite those achievements, most of European Union’s (EU’s) countries represent different interests, what can hinder further developments. China’s B&R Initiative is undoubtedly a priority in Beijing’s foreign policy. European countries should make their best to capitalize on the opportunities it provides. It seems to be possible only if European countries would have a common position vis-à-vis Beijing.